Effects of information quality on information adoption on social media review platforms: moderating role of perceived risk - Jiang, Guoyin; Liu, Fen; Liu, Wenping; Liu, Shan; Chen, Yufeng; Xu, Dongming (Data science and management, 2021)
With the integration of social media and e-commerce, social media review platforms provide consumers with a place to share information and create electronic word of mouth (e-WOM). Information from e-WOM plays an important role in consumers’ decision-making process. However, the information adoption process of users of social media review platforms remains unclear. Thus, this study builds a model to investigate how information quality affects individual information adoption on e-commerce platforms and explores the moderating effects of perceived risk on information quality, perceived diagnosticity, and information credibility. Structural equation modeling and regression analysis are used to test the proposed model. Results show that information quality consists of content quality, expression quality, and utility quality, all of which effectively affect the information adoption on socialized e-commerce platforms through perceived diagnosticity and information credibility. Findings also suggest that perceived risk positively moderates the effects of information quality on perceived diagnosticity.